Studies on the kinematics of Chinese elite man hammer athlete throwing technology - Jia, C.; Zhou, J. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study is to provide the theoretical basis for the teaching and training of the hammer throwing and improve Chinese man hammer to reach world-class as soon as possible.This paper made a 3D camera resolution on the top three men's hammer throwers in 2012 China Long Throw Open (Shizhu Wang, Kun Guo and Xiao Feng). With the comparative analysis on the related kinematic parameters of the world elite men's hammer throwers, it presents the main problems and gaps in China men's hammer throwers motion technology.